Penggunaan High Heels dan Kelelahan Kerja pada Karyawati Mal - Eta Berina Kuswardani; Arifin Arifin; Gunung Setiadi (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2018)
The Use of High Heels and Work Fatigue at The Employee Mal. Usage of high heels with standing position continuously over working will have an impact on work fatigue. This study aims to determine the relationship of usage of high heels with fatigue on employee of Mal in Banjarbaru. This study used observational method with cross sectional design. Research instruments used are Questionnaires Measuring Work fatigue Feeling and ruler. Population in this study are 120 people. Sampling technique in this study used purposive sampling technique with total samples are 36 people. Data analysis in this study used correlation test rank spearman. The results of study is The employees used high heels with low altitude are 21 people and very high altitude are 15 people, The employees did not experience fatigue are 9 people, and employees experienced low fatigue are 15 people, and employees experienced middle fatigue are 12 people, and There was no relationship between the height of shoes with fatigue on employees of Mal in Banjarbaru. The employees should use high heels with the altitude have recommended that is maximum of 5 cm, because if >5 cm will be risky to affected a disorder of health.